Effect of Processing Technology, Nanomaterial and Coupling Agent Ratio on Some Physical, Mechanical, and Thermal Properties of Wood Polymer Nanocomposites - Birinci, Emre; Kaymakci, Alperen (MDPI AG, 2023)
The goal of this study is to find out how some properties of wood-polymer nanocomposites are affected by the processing technology, the nanomaterials, and the ratio of coupling agents. To meet this objective, the extruded and dry blended samples are made from wood flour with MAPP, ZnO nanoparticles (0, 1, 3, and 5 wt%), and polypropylene. The mechanical properties of the nanocomposites improve significantly with ZnO and MAPP loading. Due to the more homogeneous structure of nanocomposites, better mechanical results are obtained with the extrusion method. With ZnO and MAPP loading, the thermal stability of nanocomposites improves. The storage and loss modulus values indicate that the processing technology of nanocomposites could be a key factor in the resistance of the materials obtained by extrusion. The storage and loss modulus of nanocomposites manufactured by the extrusion technology are determined to be higher than those of the samples produced by the dry blending method.
Keywords: nanocomposites; polypropylene; wood; processing technology; SEM; TGA; DSC; DMA